Mitochondria, Peroxisomes and Beyond—How Dual Targeting Regulates Organelle Tethering - Johannes Freitag; Thorsten Stehlik; Gert Bange (Contact, 2024)
Eukaryotic cells feature distinct membrane-enclosed organelles such as mitochondria and peroxisomes, each playing vital roles in cellular function and organization. These organelles are linked at membrane contact sites, facilitating interorganellar molecule and ion exchange. Most contact-forming proteins identified to date are membrane proteins or membrane-associated proteins, which can form very stable contacts. Recent findings suggest additional mechanistically distinct tethering events that arise from dual protein targeting. Proteins bearing targeting signals for multiple organelles, such as an N -terminal signal for mitochondria and a C -terminal signal for peroxisomes, function as tethers, fostering contacts by engaging targeting factors at both organelles. A number of dually targeted membrane proteins can contribute to contact site formation and transit from one organelle to the other as well. These interactions may enable the fine-tuning of organelle proximity, hence, adapting connections to meet varying physiological demands.